Perancangan Ambient Media sebagai Media Kampanye Pencegahan Pelecehan Seksual di Lingkungan Kampus - Tommi (Universitas Budi Luhur, 2023)
The phenomenon of sexual violence and harassment can happen anywhere and by anyone. This phenomenon often occurs also in educated environments, one of which is the campus. Ideally the place is the safest place to gain knowledge for students. So that further education is needed about this phenomenon through social campaigns on campus. To prevent future incidents, an effective solution involves using ambient media in elevators for social campaigns addressing violence and sexual harassment on campus. By utilizing this medium, the messages can be conveyed quickly and clearly to students, raising awareness and helping prevent such acts in the campus environment.